14.1k views
0 votes
16. (01.07)

An equation is shown below:
4(x - 3) - 5(x + 1) = 3
Which statement shows a correct next step in solving the equation? (1 point)
The equation can become 4x - 3 - 5x + 1 = 3 by applying the associative property of multiplication.
The equation can become 4x - 3 - 5x + 1 = 3 by applying the distributive property.
The equation can become 4x - 12 - 5x - 5 = 3 by applying the distributive property.
The equation can become 4x - 12 - 5x - 5 = 3 by applying the associative property of multiplication.
17.(01.07)
00:07:38

User PavelGP
by
5.0k points

1 Answer

5 votes

Answer:

Use the site called quetext is helps when brarnly is not

Explanation:

User Rensothearin
by
5.1k points